Complications in pulmonary vein isolation in the Netherlands Heart Registration differ with sex and ablation technique. Issue 2 (3rd November 2020) - Mol, Daniel; Houterman, Saskia; Balt, Jippe C; Bhagwandien, Rohit E; Blaauw, Yuri; Delnoy, Peter-Paul H; van Driel, Vincent J; Driessen, Antoine H; Folkeringa, Richard J; Hassink, Rutger J; van Huysduynen, Bart Hooft; Luermans, Justin G; et al.
Abstract: Aims : Pulmonary vein isolation (PVI) has become a cornerstone of the invasive treatment of atrial fibrillation. Severe complications are reported in 1–3% of patients. This study aims to compare complications and follow-up outcome of PVI in patients with atrial fibrillation. Methods and results : The data were extracted from the Netherlands Heart Registration. Procedural and follow-up outcomes in patients treated with conventional radiofrequency (C-RF), multielectrode phased RF (Ph-RF), or cryoballoon (CB) ablation from 2012 to 2017 were compared. Subgroup analysis was performed to identify variables associated with complications and repeat ablations. In total, 13 823 patients (69% male) were included. The reported complication incidence was 3.6%. Patients treated with C-RF developed more cardiac tamponades (C-RF 0.8% vs. Ph-RF 0.3% vs. CB 0.3%, P ≤ 0.001) and vascular complications (C-RF 1.7% vs. Ph-RF 1.2% vs. CB 1.3%, P ≤ 0.001). Ph-RF was associated with fewer bleeding complications (C-RF: 1.0% vs. Ph-RF: 0.4% vs. CB: 0.7%, P = 0.020). Phrenic nerve palsy mainly occurred in patients treated with CB (C-RF: 0.1% vs. Ph-RF: 0.2% vs. CB: 1.5%, P ≤ 0.001). In total, 18.4% of patients were referred for repeat ablation within 1 year. Female sex, age, and CHA2 DS2 -VASc were independent risk factors for cardiac tamponade and bleeding complications, with an adjusted OR for female patients of 2.97 (95% CI 1.98–4.45) and 2.02 (95% CI 1.03–4.00) respectively. Conclusion : The reported complication rate during PVI was low. Patients treated with C-RF ablation were more likely to develop cardiac tamponades and vascular complications. Female sex was associated with more cardiac tamponade and bleeding complications. Graphical Abstract: